Release tension. (Economist, 2026)
The article focuses on how leading AI labs are using exclusivity and staged releases of advanced models as both a marketing strategy and a security measure in a highly competitive industry. Topics include Anthropic's limited rollout of its "Mythos" model to control cyber-security risks, concerns over model theft and "distillation" by rival firms, and broader industry constraints such as limited computing power and rising demand for frontier AI systems.